MYBIOTA: A birth cohort on maternal and infant microbiota and its impact on infant health in Malaysia - Eow, Shiang Yen; Gan, Wan Ying; Jiang, Tiemin; Loh, Su Peng; Lee, Ling Jun; Chin, Yit Siew; Than, Leslie Thian Lung; How, Kang Nien; Thong, Pui Ling; Liu, Yanpin; Zhao, Junying; Chen, Lijun (Frontiers in Nutrition, 2022)
Background The microbiota plays a key role in early immunity maturation that affects infant health and is associated with the development of non-communicable diseases and allergies in later life. Objective The MYBIOTA is a prospective mother-infant cohort study in Malaysia aiming to determine the association between gut microbiota with infant health (temperament, gastrointestinal disorders, eczema, asthma, and developmental delays) in Selangor, Malaysia. Methods Pregnant mothers will be enrolled in their first trimester of pregnancy, and follow-ups will be done for infants during their first year of life. Maternal-infant biological samples (blood, feces, saliva, urine, and breast milk), anthropometric, dietary, and clinical information will be collected at different time points from early pregnancy to 12 months postpartum. Discussion This study could provide a better understanding of the colonization and development of the gut microbiome during early life and its impact on infant health. Clinical trial registration https://clinicaltrials.gov/, identifier NCT04919265.